EKSPLORASI MAKNA PARTISIPASI MASYARAKAT DALAM PENGANGGARAN (Sebuah Studi Fenomenologi) - Sulton Afriansyah (Universitas Negeri Malang, 2016)
Abstract:Meaning Exploration of Citizen Participation in Budgeting, a Phenomenology Study.Thisstudy is aimed at understanding the actors of Public Empowerment Program of Kediri government,particularly at “Harmony” Sub-District, regarding the citizen participation in budgeting. The researchmethod of the study is a transcendental phenomenology. The results of this study reveal a number ofphenomena, first, the program’s actors understand the citizen’s participation on budget planning as atrust. Second, in implementing the budget, the citizen’s participation is interpreted as a job. Finally, thecitizen participation in budget supervision is interpreted as a guarantee. Hence the conclusion drawnis the government programs must be implemented through a process of interaction between the govern-ment and the public on the basis of trust by working together and of guarantee that the programs canrun well and successfully.Keywords:Meaning, Citizen Participation, Budgeting.